'He States That This is the Most Lovely Building He Has Ever Had the Pleasure of Seeing . . . ': The Travel Writing and Collecting of Frederick Horniman. Issue 2 (1st December 2021) - Nutting, Ryan
Abstract: The travel journal, collecting, and exhibition of objects by museum founder, tea merchant and Member of Parliament Frederick Horniman (1835–1906) in the late nineteenth century demonstrate how material objects exemplify travel writing. Through an examination of objects he collected and later interpreted at the Horniman Free Museum, this article presents a case study of how collecting activities mirror and serve as a form of travel writing. This article presents a new model for understanding, beyond the written word, how travelers can capture the experience of a foreign expedition through the collecting and interpretation of objects.